Biliary peritonitis due to perforation of an intrahepatic canaliculus - Laca, Emilio; Escobar, Washington; Cardoso Lareo, Federico (Cirugía del Uruguay, 1975)
Biliary peritonitis due to spontaneous perforation of small intrahepatic bile ducts are extremely rare. Comments are made on what is presumed to be the first case in this country. Although diagnosis is difficult, a critical study of the cases published, gives the authors ground to state that, in an aged female patient with a clinical history of biliary disorders, the association of peritonitis and jaundice, make it reasonable to suspect its existance. It is believed that hypertensión of the biliary tract is a predominant factor in causing this condition.